2021
DOI: 10.47278/journal.ijvs/2021.046
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Circulating Foot and Mouth Disease Virus in Egypt During 2018-2020

Abstract: Foot and Mouth Disease (FMD) is a contagious viral disease with high economic losses and primary animal health concerns. FMDV type SAT2 is endemic in Egypt since 2012. This work aimed to characterize the circulating FMDV SAT2 strains genetically in Egypt from 2018 to 2020. A total of 209 vesicular fluids and tongue epithelium were collected from infected cattle and buffaloes in Sharkia, Ismailia, and Dakhlia provinces. All samples were examined by real-time PCR and conventional PCR for FMDV using pan- serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Infectious diseases of animals including parasitic infestations pose significant threats to health and productivity potential of animals ( 113 116 ) which leads to heavy economic losses ( 117 – 122 ). Parasitic infections lead to chronic and debilitating types of diseases and have zoonotic implications as well ( 3 , 123 – 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases of animals including parasitic infestations pose significant threats to health and productivity potential of animals ( 113 116 ) which leads to heavy economic losses ( 117 – 122 ). Parasitic infections lead to chronic and debilitating types of diseases and have zoonotic implications as well ( 3 , 123 – 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases such as parasitic infestations are important health problems in both animals and humans ( 46 50 ), which cause economic losses and severe illness ( 51 – 56 ). In this study, a molecular description of P. epiclitum isolates from sheep and goats was reported for the first time in Pakistan based on the mt cox 1 gene as mtDNA remains an important marker in exploring intraspecific variation due to maternal inheritance, conserved structure, higher evolution rate, high genetic divergence, and absence of recombination ( 57 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases, including parasitic infestations, are important health problems in both animals and humans (1)(2)(3)(4), which cause economic losses and severe illness (5)(6)(7)(8)(9)(10). Parasites are capable of causing acute, chronic, and debilitating types of diseases, leading to production losses in animals (11)(12)(13)(14)(15), and many pieces of research have shown the positive role of alternative/complementary medicine in treating parasitic diseases.…”
Section: Introductionmentioning
confidence: 99%